2014
DOI: 10.1155/2014/459549
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor-Mediated Neuroprotective Effect of theScutellaria baicalensisGeorgi Extract on the Excitotoxic Neuronal Cell Death in Primary Rat Cortical Cell Cultures

Abstract: The objective of the current research work was to evaluate the neuroprotective effect of the ethanol extract of Scutellaria baicalensis (S.B.) on the excitotoxic neuronal cell death in primary rat cortical cell cultures. The inhibitory effects of the extract were qualitatively and quantitatively estimated by phase-contrast microscopy and lactate dehydrogenase (LDH) assays. The extract exhibited a potent and dose-dependent inhibition of the glutamate-induced excitotoxicity in the culture media. Further, using r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The ethanol extract of Scutellaria baicalensis Georgi. protects cell cultures of primary rat cortical neurons against glutamate toxicity by binding with the glycine-binding site of the N-methyl-D-aspartate receptor [ 83 ]. Estrogen and insulin-like growth factor-1 (IGF-1) receptors facilitate NTF stimulation and neuronal protection by various flavonoids (i.e., calycosin, luteolin, ginsenoside Rg1, genistein) in the PD rat model [ 84 , 85 ].…”
Section: Neurotrophic Activity Of Natural Products For Neuroprotectionmentioning
confidence: 99%
“…The ethanol extract of Scutellaria baicalensis Georgi. protects cell cultures of primary rat cortical neurons against glutamate toxicity by binding with the glycine-binding site of the N-methyl-D-aspartate receptor [ 83 ]. Estrogen and insulin-like growth factor-1 (IGF-1) receptors facilitate NTF stimulation and neuronal protection by various flavonoids (i.e., calycosin, luteolin, ginsenoside Rg1, genistein) in the PD rat model [ 84 , 85 ].…”
Section: Neurotrophic Activity Of Natural Products For Neuroprotectionmentioning
confidence: 99%
“…The extact could also protect animals from global cerebral ischemia and MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine)-induced Parkinson's disease, and protect cortical and neuronal cells from glutamate, NMDA ( N -methyl-D-aspartic acid), and H 2 O 2 induced toxicity in vitro (Yang et al. 2014; Cao et al. 2016; Li et al.…”
Section: Pharmacological Activities Of Extracts and Major Compoundsmentioning
confidence: 99%
“…In rat primary mesencephalic cultures, baicalein inhibited the glutamate -induced intracellular calcium ion increase. Baicalein also showed neuroprotective effects on excitotoxic neuronal cell death in primary rat cortical cell cultures (Yang et al, 2014). Interestingly, an improved drugs screening system revealed that baicalein not only ameliorates the Aβ-induced depolarization of neurons, but also possibly functions as an antagonist of AMPA and NMDA receptors (Lin et al, 2017).…”
Section: Baicalein Inhibits Excitotoxicitymentioning
confidence: 99%